Models and methodologies in distance education - Mason, Robin (2008)
This paper looks at the evolution of e-learning from distance education. It outlines a simple classification of e-learning models and then considers blended learning as a separate category. Course design for e-learning includes a discussion of course planning, media use and assessment.